Analisis Saluran dan Margin Pemasaran Komoditas Melon Kirani di Kebun Enha Lima Kabupaten Pelalawan Provinsi Riau - Ernawati; Hasanudin; Wahyudi Zikri; Adriansyah (An Nafi': Multidisciplinary Science, 2025)
This study aims to analyze 1) determine the marketing channels of melons found in Enha Lima Farm, 2) determine the amount of margin of each institution and the total of the entire marketing of melons in Enha Lima Farm. Forms of kirani melon marketing channels in Enha Lima Garden are direct channel marketing and indirect marketing. From these forms of marketing, the amount of margin obtained by channel I (indirect marketing) is Rp.10,000 consisting of a margin for collecting traders of Rp.5,000/Kg, and for retail traders of Rp. 5,000/Kg. Meanwhile, channel II (direct marketing) has no margin because it does not go through marketing institutions or intermediaries where farmers sell melons directly to end consumers. So that channel II (direct marketing) can be said to be profitable for Enha Lima garden farmers. The high value of the margin is influenced by the low value of marketing costs incurred. So that the channel is most profitable for producers or at the farm level. While the Farmer's share value of all channels is said to be efficient, the percentage of marketing channel level I is 66.66%, marketing channel II is 100%.